Computational modelling of mechanically induced electrophysiological alterations of axons and nerve - Kwong, M (2018)
In the last decade, traumatic brain injuries (TBIs) and spinal cord injuries (SCIs) has become one of the most scrutinised medical challenges of our time. However, the lower quality of life experienced by the sufferer and the associated socio-economic cost of both TBI and SCI remain a huge burden for society. There is currently no reliable way to evaluate the level of functional damage caused by TBI and SCI related mechanical forces without invasive examination. The types of axonopathy involved in such injuries are the combinations of coupled mechanical-electrophysiological phenomena at multiple length and time scales, extremely challenging to approach by experimental means alone. It is therefore highly desirable to complement experimental studies with computational work to further the understanding of such multiscale problems. This thesis firstly proposes a novel 3D finite element framework coupling mechanics and electrophysiology to model cellular and subcellular phenomena, such as nerve dislocation and membrane damage by micropipette. The former study shows that 1D simulations focussing solely on the stretch component of the axonal damage are unable to capture the same electrophysiological damage that a 3D framework predicts. The latter study shows that local membrane deformation can lead to electrophysiological alterations at the axonal level solely through geometrical effects and without the need to account for ion channel activity alterations. This was demonstrated for micropipette suction in a patch clamp where the consideration of the 3D flow of current was sufficient to alter its electrophysiology, offering an alternative explanation to the damage mechanism hypothesised by published experimental work. At the axonal and tissue scale, previous models have often simplified the modelling of damage by using a single axon model. It is however unclear whether an altered axonal electrophysiology can truly be representative of the compound electrophysiology of multiple axons or fibre. Three different models: axonal, fibre and tissue level models, were evaluated and compared for their ability to model macroscale electrophysiology deficits. The results of the three models suggest that the recovery of compound action potential amplitude post-mechanical stretch can not be straightforwardly scaled from axonal level to fibre level. Furthermore, the electrophysiological recovery may not be solely dependent on mechanical recovery of the tissue. This thesis identified the need for scale specific models in the context of TBI and SCI. In particular, lipid bilayer membrane geometrical distortion following mechanical insult at the subcellular scale and functional tissue alteration at the tissue scale both require a different approach. The models proposed herein successfully identify mechanisms overlooked in previous experimental literature. In order to fully capture experimental behaviour, future models will need to account for other mechanisms such as mechanoporation, reorganisation of paranodal junctions and injury related Calcium ion imbalance.